A INFORMAÇÃO COMO UM INDICADOR DE QUALIDADE DA CARNE BOVINA - ESCOBAR, Loraine Saldanha; PIAZZON, Cleiton José; FLORES, Hugo Pereira; GOMES, Ana Carolina Alves; NASCIMENTO, Julia Dias do; OLIVEIRA, Dalton Mendes de (ANAIS DO ENIC, 2018)
-